Characterization of the Activity of Croton tiglium Oil in Hetter's Very Heavy Phenol-Croton Oil Chemical Peels - Justo, Aline S.; Lemes, Bruna M.; Nunes, Bruna; Antunes, Kevin A.; Capote, Anna Claudia M O; Lipinski, Leandro C.; Campagnoli, Eduardo B.; Emiliano, Janaina; Meurer, Eduardo C.; Ezemma, Ogechi; Miot, Helio A. [UNESP]; Beltrame, Flávio L; et al. (Wolters Kluwer, 2021)
BACKGROUND: Croton oil (CO) is used by dermatologists and plastic surgeons in deep chemical peels. It is mixed with phenol, water, and a soap in Baker-Gordon's or Hetter's formulas. There is controversy as to whether CO or phenol is the active agent in the dermal effect of deep chemical peels. OBJECTIVE: To better clarify the role of CO in deep peels, by identification of active compounds in commercially available CO in the United States and biological effects in vivo. MATERIALS AND METHODS: Liquid chromatography-tandem mass spectrometry on CO and a domestic pig model experiment using 3 different formulas: G1: 5% Septisol (SEP), G2: 1.6% croton oil in 35% phenol with 5% SEP, and G3: 35% phenol with 5% SEP. RESULTS: Liquid chromatography-tandem mass spectrometry indicated the presence of phorbol esters. G1 was null overall. Extent of the coagulative necrosis: G2 > G3. Vascular ectasia: G2 > G3. Inflammation pattern: intense neutrophilic inflammatory band in G2 versus mild, sparse, perivascular mononuclear cell infiltrate in G3. Neocollagenesis: pronounced in G2, negligible in G3. CONCLUSION: Coagulative necrosis of the epidermis, superficial fibroblasts, and vasculature can be attributed to the action of phenol. Phorbol esters on CO could be responsible for the dense deep acute inflammation and the distinctive neocollagenesis.